Impact of psoas muscle index on short-term outcome after living donor liver transplantation - Izumi, Toshio; Watanabe, Jota; Tohyama, Taiji; Takada, Yasutsugu (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Living donor liver transplantation is an operation with high morbidity and mortality rates. The purpose of this study was to examine factors affecting the short-term outcome after living donor liver transplantation. Materials and Methods: Forty-seven adult patients who underwent living donor liver transplantation from September 2001 to December 2014 were included. Short-term post-transplant outcomes were evaluated in terms of the onset of postoperative complications of grade 3a and above (Clavien–Dindo classification) and postoperative 120-day mortality. Univariate and multivariate analyses were used to determine possible predictive factors among perioperative variables such as preoperative psoas muscle index (PMI), blood laboratory test results, perioperative nutritional therapy, and operative factors. Results: Lower PMI (lower than the first quartile of PMI of donors), higher blood urea nitrogen level (≥14 mg/dL), and blood type incompatibility were independent risk factors for the development of postoperative complications. The 120-day survival rates were significantly lower for the lower PMI group (n=30, 66.7%) than for the higher PMI group (n=17, 94.1%, p=0.034). Conclusion: A significant correlation was observed between preoperative PMI and short-term postoperative outcomes. Sarcopenia estimated by PMI may serve as a measure of patient frailty and a target for risk stratification.